Outline of the U.S. legal system. - United States. Department of State. Bureau of International Information Programs (Washington, D.C. Bureau of International Information Programs, United States Department of State, 2004)
Every business day, courts throughout the United States render decisions that together affect many thousands of people. Some affect only the parties to a particular legal action, but others adjudicate rights, benefits, and legal principles that have an impact on all Americans. This book surveys that system. Much of the discussion explains how U.S. courts are organized and how they work. This introduction seeks to familiarize readers with the basic structure and vocabulary of American law, and afford a sense of how the U.S. legal system has evolved to meet the needs of a growing nation and its ever more complex economic and social realities.
Introduction: The U.S. legal system -- Ch. 1. History and organisation of the federal judicial system -- Ch. 2. History and organisation of state judicial systems -- Ch. 3. Juridiction and policy-making boundaries -- Ch. 4. Lawyers, litigants, and interest groups in the judicial process -- Ch. 5. The criminal court process -- Ch. 6. The civil court process -- Ch. 7. Federal judges -- Ch. 8. Implementation and impact of judicial policies -- The Constitution of the United States -- Amendments to the Constitution of the United States.
"Outline of the U.S. Legal System is a publication of the United States Dept. of State. Chapters 1 through 8 are adapted with permission from the book "Judicial Process in America", 5th ed., by Robert A. Carp and Ronald Stidham, published by Congressional Quartlerly, Inc., (c)2001"--Page 108.
Keywords: Federal government -- United States; Separation of powers -- United States; Law -- Political aspects -- United States; Justice, Administration of -- United States; Law -- United States -- Interpretation and construction; Courts -- United States